Quantum theory for chemical applications : from basic concepts to advanced topics - Autschbach, J. (Jochen) (Oxford University Press, 2021)
"Quantum Theory for Chemical Applications (QTCA) Quantum theory, or more specifically, quantum mechanics is endlessly fascinating, curious & strange, and often considered to be difficult to learn. It is true that quantum mechanics is a mathematical theory. Its scope, its predictions, the wisdom we gain from its results, all these become fully clear only in the context of the relevant equations and calculations. But the study of quantum mechanics is definitely worth the effort, and - as I like to tell my students- it is not rocket science"--